Bone Repairment via Mechanosensation of Piezo1 Using Wearable Pulsed Triboelectric Nanogenerator. Issue 30 (1st June 2022) - Wang, Bingjin; Li, Gaocai; Zhu, Qianqian; Liu, Weifang; Ke, Wencan; Hua, Wenbin; Zhou, Yiming; Zeng, Xianlin; Sun, Xuhui; Wen, Zhen; Yang, Cao; Pan, Yue
Abstract: Bone repair in real time is a challenging medical issue for elderly patients; this is mainly because aged bone marrow mesenchymal stem cells (BMSCs) possess limited osteogenesis potential and repair capacity. In this study, triboelectric stimulation technology is used to achieve bone repair via mechanosensation of Piezo1 by fabricating a wearable pulsed triboelectric nanogenerator (WP‐TENG) driven by human body movement. A peak value of 30 µA has the optimal effects to rejuvenate aged BMSCs, enhance their osteogenic differentiation, and promote human umbilical vein endothelial cell tube formation. Further, previous studies demonstrate that triboelectric stimulation of a WP‐TENG can reinforce osteogenesis of BMSCs and promote the angiogenesis of human umbilical vein endothelial cells (HUVECs). Mechanistically, aged BMSCs are rejuvenated by triboelectric stimulation via the mechanosensitive ion channel Piezo1. Thus, the osteogenesis potential of BMSCs is enhanced and the tube formation capacity of HUVECs is improved, which is further confirmed by augmented bone repair and regeneration in in vivo investigations. This study provides a potential signal transduction mechanism for rejuvenating aged BMSCs and a theoretical basis for bone regeneration using triboelectric stimulation generated by a WP‐TENG. Abstract : A body movement–driven pulsed triboelectric nanogenerator (P‐TENG) system is fabricated to generate stable pulsed current output. Senescent bone marrow mesenchymal stem cells (BMSCs) get rejuvenated under the triboelectric stimulation manifesting with enhanced osteogenic capacity and increased pro‐tube formation of human umbilical vein endothelial cells, providing a theoretical basis for bone regeneration and repair through triboelectric technology.